2018
DOI: 10.1590/01047760201824042531
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles-Based Wood Preservatives: The Next Generation of Wood Protection?

Abstract: Review on biocides nanoparticles. Nanoparticles-based wood preservatives. Nanoparticles biocides applied on wood protection. Protection against biodeterioration through nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
(93 reference statements)
0
24
0
2
Order By: Relevance
“…Screening studies have shown that a 1 wt.% dispersion of 30 nm Cu, Zn, and B nanoparticles significantly inhibits the growth of brown rot fungi, while completely eradicating other non-fungal wood pests (termites, molds). Metal oxide nanoparticles (e.g., ZnO) are less effective as fungicides [ 62 ].…”
Section: Antifungal Wood Preservationmentioning
confidence: 99%
“…Screening studies have shown that a 1 wt.% dispersion of 30 nm Cu, Zn, and B nanoparticles significantly inhibits the growth of brown rot fungi, while completely eradicating other non-fungal wood pests (termites, molds). Metal oxide nanoparticles (e.g., ZnO) are less effective as fungicides [ 62 ].…”
Section: Antifungal Wood Preservationmentioning
confidence: 99%
“…However, there is a growing interest in the development of purely inorganic or inorganic-rich alternative solutions stimulated by new requirements and regulations such as the reduction of volatile organic compounds emissions or the demand for ultraviolet-resistant and fire-retardant products. A large number of research works have been published in recent years on surface coatings of wood by depositing thin layers of various inorganic nanoparticles (e.g., TiO 2 , SiO 2 , Al 2 O 3 , ZnO, CuO) or even metallic particles (e.g., Ag, Zn, Cu, Al) using techniques such as sol-gel impregnation, or physical and chemical vapor deposition [1][2][3][4]. Silicate-based coating systems are also potential inorganic alternatives that have the added advantage of being formulated for application by any end user with a minimum of experience and for wood renovation.…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of the material depends on the addition of toxic substances or repellents, known as wood preservatives, with a focus on increasing the resistance to deterioration and durability (Lepage et al, 2017). In Brazil, the most used treatments are those based on chromed copper arsenate (CCA) and chromed copper borate (CCB) (Vidal et al, 2015;Borges et al, 2018).…”
Section: Introductionmentioning
confidence: 99%